Financial Behaviors and Their Predictive Power on Stress: A Neutrosophic QCA Approach - Suly Sendy Pérez-Castañeda; Blanca Estela Hernández-Bonilla; Dorie Cruz-Ramírez; Beatriz Sauza-Ávila; Gisela Janeth Espinosa-Martínez (Neutrosophic Sets and Systems)
This study examines the relationship between financial behaviors and financial stress levels in a representative sample of Mexican adults (N = 352). Two indices were constructed: the Financial Behavior Index – Psychological Factors (FBIPF) and the Financial Stress Index (FSI). To study the relationship between the two aspects, classical statistical correlation methods were replaced by the Neutrosophic Qualitative Comparative Analysis (NQCA). NQCA is a generalization of Crisp QCA and Fuzzy QCA to the neutrosophic framework, where, in addition to a truth value, an indeterminacy and falsity value are taken into account. In this way, indeterminacy and uncertainty are considered, gaining accuracy. On the other hand, the QCA method is a more flexible alternative to statistical correlation, since it uses set-based measures in situations where there are causal relationships between concepts, rather than equivalence. So, the existence of multicausality is modeled. The method is also an intermediate technique between qualitative and quantitative methods.